The Use of Describe and Draw Technique in Improving Speaking Skill - Mgs. Sulaiman; Sherly Marliasari; Diah Alip Utami (Universitas KH. Mukhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2024)
This research was aimed at figuring out whether or not it was effective to use describe and draw technique to improve speaking skills of the tenth grade students of SMA Aisyiyah 1 Palembang. This research applied a pre-experimental research design in line with One-Group Pretest-Posttest. The population of the study was the tenth grade students of SMA Aisyiyah 1 Palembang and 19 of them used as the samples chosen by using convenience sampling technique. To analyze the data, the researchers used Match T-test. The results showed that t-test obtained was 4.209 and it was higher than the critical value of t-table was 2.101 with (df) n= 18 at the level of significance 0.05 (5%) for two-tailed test which indicated that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. Since t-obtained was higher than the value of t-table, it can be glean from that Describe and Draw Technique was effective in improving speaking skills of the tenth grade students of SMA Aisyiyah 1 Palembang.